The Connection Between Teachers' Mindsets and Methods of Assessment in the Classroom - Arcegono, Winda J.; Sumandal, Mercedes B.; Gavilo, Daisy Q.; Lanzaderas, Rhea A.; Lanzaderas, Riza A.; Magracia, Christine C.; Nuñala, Anecel; Mohammad, Nhelbourne K. (Jurnal Genesis Indonesia, 2023)
This study aims to understand the connection between teachers' mindset approaches and their mindset toward classroom assessment. The issue was to discuss the efficiency and effectiveness of classroom assessment with the different perspectives of teachers, whether new applicants or previous teachers. We continue to understand the mindset and its components for a constructive evaluation as it develops and enhances the student's engagement in the teaching/ learning process that elevates the level of performance of students in the classroom. In conclusion, the growing mindset is more favourable because this kind of positive mental attitude aims for fairness that involves the relationship between the teacher's philosophy and approaches to learning. As a result, the findings of this study not only disclose the implicit and innate attitudes of teacher candidates regarding learning and assessment but also offer an empirical basis for the development of responsive and focused teacher education in assessment.